Potensi Penerapan Deep Learning dalam Penguatan Karakter Profil Pelajar Pancasila: Sebuah Tinjauan Literatur Sistematis: Penelitian - Ambrosius Tode Peya Nia Do; Benediktus Rahawarin; Siti Zulaikha; Muh. Takdir (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the potential and challenges of integrating Deep Learning (DL) into character education aligned with the Profile of Pancasila Students. The method employed is a literature review of recent studies on DL applications in character development, focusing on how this technology supports dimensions such as independence, collaboration, critical thinking, and lifelong learning. The findings indicate that DL has significant capabilities in personalizing learning, predicting student learning behavior, and facilitating reflective and value-driven learning activities. However, its implementation faces several challenges, including inadequate infrastructure, low digital literacy among educators, and ethical issues such as data privacy and algorithmic bias. Moreover, existing literature tends to emphasize DL’s functional benefits rather than its specific architectural or methodological details, highlighting the need for further research on the most effective and ethical DL models for student character development.